x*log(x)
d --(x*log(x)) dx
Применяем правило производной умножения:
ddxf(x)g(x)=f(x)ddxg(x)+g(x)ddxf(x)\frac{d}{d x} f{\left(x \right)} g{\left(x \right)} = f{\left(x \right)} \frac{d}{d x} g{\left(x \right)} + g{\left(x \right)} \frac{d}{d x} f{\left(x \right)}dxdf(x)g(x)=f(x)dxdg(x)+g(x)dxdf(x)
f(x)=xf{\left(x \right)} = xf(x)=x; найдём ddxf(x)\frac{d}{d x} f{\left(x \right)}dxdf(x):
В силу правила, применим: xxx получим 111
g(x)=log(x)g{\left(x \right)} = \log{\left(x \right)}g(x)=log(x); найдём ddxg(x)\frac{d}{d x} g{\left(x \right)}dxdg(x):
Производная log(x)\log{\left(x \right)}log(x) является 1x\frac{1}{x}x1.
В результате: log(x)+1\log{\left(x \right)} + 1log(x)+1
Ответ:
log(x)+1\log{\left(x \right)} + 1log(x)+1
1 + log(x)
1 - x
-1 --- 2 x